Unionized Acetate Degradation at 45ºC Anaerobic Digestion: Kinetics and Inhibition - Mohd, Nuruol Syuhadaa; Li, Baoqiang; Riffat, Rumana (HARD Publishing, 2018)
This study demonstrated the degradation of unionized acetate in anaerobic digestion at 45ºC through the identification of kinetics and inhibition parameters. The kinetic parameters, Ks and rmax, were determined using Monod-based model for three different conditions, namely uninhibited, inhibited, and systems with high substrate condition. The Ks values for uninhibited condition were in the range of 0.124 to 0.191 mg/L as unionized HAc. Ks value of inhibited condition were at 0.027 mg/L as unionized HAc. Ks values for systems with high substrate condition were found to be in the range of 0.237 to 0.279 mg/L as unionized HAc. As for rmax, a 35ºC anaerobic digestion system showed the highest value at 0.166 mg/L/day – greater than the values of all 45ºC systems under all experimental conditions. Additionally, the inhibition parameter KI was also determined using the Michaelis-Menten model. The parameter was determined for inhibitory conditions resulting from high free NH3 content. The inhibition type was uncompetitive with KI value of 0.072 mg/L as unionized HAc. The outcomes suggested that the methanogens responsible for the digestion process at 45ºC were thermo-tolerant acetate-utilizing methanogens of Methanosarcinaceae species, and the system will be totally inhibited with the presence of high free NH3 content. © 2019, HARD Publishing Company. All rights reserved.